Disseminated cryptococcosis and hepatitis C virus infection: A fatal co-infection - Ranjana Rohilla; Suneeta Meena; Neelam Kaistha; Anusha Krishna Raj; Pratima Gupta (Mazandaran University of Medical Sciences, 2019)
Background and Purpose: We report a case of disseminated cryptococcosis in a treatment-naïve patient, incidentally diagnosed with hepatitis C virus (HCV) infection and renal parenchymal disease. The patient succumbed to death given the very late diagnosis of the disease. Case report: A 54-year-old male presented with the chief complaints of abdominal pain, chest pain, and phlegmy cough for a month. There was a past history of decreased urine output, lower limb swelling, and fever lasting for 15-20 days. After a general physical examination, the differential diagnosis of hepatitis C-related liver disease with hepatic encephalopathy, disseminated tuberculosis, and septic shock was made. Radiological examination revealed renal parenchymal disease on ultrasound abdomen and opacity with reticulonodular opacity in the bilateral lung zones. In laboratory investigations, serum reactive sample was tested for anti-HCV antibodies. In addition, Cryptococcus var grubii was identified in blood culture using the matrix-assisted laser desorption ionization-time of flight mass spectrometry (Bruker Daltonics, Germany). The patient succumbed to death before the initiation of any specific antifungal therapy. Conclusion: Cryptococcosis-HCV co-infection is a fatal condition with a fulminant course that might be difficult to treat.